Gastrointestinal parasites in goats from Monte Castelo, Santa Catarina, Brazil Parasitas gastrintestinais em caprinos de Monte Castelo, Santa Catarina, Brasil - Cardoso C.P. (2012)
This study was carried out with the aim of estimating the degree of gastrointestinal helminth infection in goats on the Northern Plateau of Santa Catarina. Twelve young females and 11 adult females were used. Every 28 days, feces samples were taken to quantify the nematode eggs per gram of feces (EPG). Larval culturing was performed on a pool of positive samples from the same group. The fecal egg counts (FECs) ranged from zero to 10,400 EPG in the young group and zero to 7,600 EPG in the adult group. The mean FECs were between 583.3 and 4441.7 in the young group and between 418.2 and 2181.8 in the adult group. Eggs of the order Strongylida and genera Moniezia and Toxocara, and oocysts of Coccidia, were observed. The young animals were more affected and Haemonchus was the most prevalent genus in the samples.